-54
2007-05-25 14:14:17
·
answer #1
·
answered by BotanyDave 5
·
0⤊
0⤋
Multiply.(–6)(9)=-54
2007-05-25 21:17:36
·
answer #2
·
answered by Anonymous
·
0⤊
0⤋
One way to think about this might be to write -6 as (-1)(6).
Then (-6)(9) = (-1)(6)(9)
But you know that 6 x 9 is 54, so this is equal to (-1)(54). That's clearly -54.
2007-05-25 21:25:08
·
answer #3
·
answered by Anonymous
·
0⤊
0⤋
A positive and a negative number multiplied by each other is a negative number. 6 times 9 is 54 so -6 times 9 is -54
or -6(9) = (-6)+(-6)+(-6)+(-6)+(-6)+(-6)+(-6)+(-6)+(-6)
= (-12)+(-12)+(-12)+(-12)+(-6)
=(-24)+(-24)+(-6)
=(-48)+(-6)
=-54
2007-05-25 21:23:12
·
answer #4
·
answered by A confused bio student 2
·
0⤊
0⤋
when you multiply a negative number by a positive number, the answer is a negative number
-6 x 9 = -54
2007-05-25 21:14:33
·
answer #5
·
answered by 7
·
0⤊
0⤋
-54. The six is negative and the nine is positive. A positive mutiplied by a negative yields a negative. A negative times a negative yields a positive. If the numbers were (-6)(-9) then the answer would just be 54
2007-05-25 21:16:12
·
answer #6
·
answered by Queen JJ 2
·
0⤊
0⤋
Keep in mind that parentheses are used to indicate multiplication in the world of math.
In other words, (-6) (9) = -6 x 9 = -54
Guido
2007-05-25 21:38:11
·
answer #7
·
answered by Anonymous
·
0⤊
0⤋
A positive times a negative is always a negative. Therefore, the answer is - 54.
2007-05-25 21:20:36
·
answer #8
·
answered by livelovelaugh 3
·
0⤊
0⤋
-6*9=-54
Positive times a negative = negative
2007-05-25 22:00:54
·
answer #9
·
answered by Gamerguy 2
·
0⤊
0⤋
-6(9) = -54!
2007-05-25 21:25:07
·
answer #10
·
answered by wannalala 3
·
0⤊
0⤋